Case Report: Cadonilimab plus anlotinib with radiotherapy for lung adenocarcinoma with pancreatic metastasis in later-line therapy - Yang, Jianquan; Li, Zixin; Pang, Xuezhou; Zhang, Yakun; Zeng, Beilei; Gui, Yan; Ma, Daiyuan (Frontiers in Immunology, 2025)
Patients with advanced lung adenocarcinoma lacking driver gene mutations face the clinical dilemma of limited treatment options and poor prognosis in later-line therapy. Although immune checkpoint inhibitors (ICIs) combined with anti-angiogenic agents offer a promising approach, the optimal treatment strategy remains to be explored. In this report, we present a case of advanced lung adenocarcinoma with pancreatic metastasis treated with cadonilimab plus anlotinib and radiotherapy to the pancreatic lesion, resulting in 11 months of progression-free survival (PFS) and only minor side effects. This outcome suggests the potential value of cadonilimab and anlotinib in later-line therapy for advanced lung adenocarcinoma and provides a possible new treatment option for such patients.